An improved hybrid algorithm for improving quality parameters in MANETs. (21st January 2020) - Gupta, Rohan; Singh, Gurpreet
A mobile ad hoc network (MANET) includes wireless mobile nodes that animatedly create a temporary system without requiring a central organisation or an infrastructure. The quality of service (QoS) allows a movable network to integrate wired or wireless systems. QoS-aware algorithms intend to discover a stable route among the source and target nodes that suits the QoS constraints. The proposed algorithm has improved QoS parameters, i.e., throughput, jitter and delay in comparison to different variants of ant colony optimisation and particle swarm optimisation.